The geodynamic and limnological evolution of Balkan Lake Ohrid, possibly the oldest extant lake in Europe. (31st October 2022) - Wagner, Bernd; Tauber, Paul; Francke, Alexander; Leicher, Niklas; Binnie, Steven A.; Cvetkoska, Aleksandra; Jovanovska, Elena; Just, Janna; Lacey, Jack H.; Levkov, Zlatko; Lindhorst, Katja; Kouli, Katerina; et al.
Abstract : Studies of the upper 447 m of the DEEP site sediment succession from central Lake Ohrid, Balkan Peninsula, North Macedonia and Albania provided important insights into the regional climate history and evolutionary dynamics since permanent lacustrine conditions established at 1.36 million years ago (Ma). This paper focuses on the entire 584‐m‐long DEEP sediment succession and a comparison to a 197‐m‐long sediment succession from the Pestani site ~5 km to the east in the lake, where drilling ended close to the bedrock, to unravel the earliest history of Lake Ohrid and its basin development. 26 Al/ 10 Be dating of clasts from the base of the DEEP sediment succession implies that the sedimentation in the modern basin started at c . 2 Ma. Geophysical, sedimentological and micropalaeontological data allow for chronological information to be transposed from the DEEP to the Pestani succession. Fluvial conditions, slack water conditions, peat formation and/or complete desiccation prevailed at the DEEP and Pestani sites until 1.36 and 1.21 Ma, respectively, before a larger lake extended over both sites. Activation of karst aquifers to the east probably by tectonic activity and a potential existence of neighbouring Lake Prespa supported filling of Lake Ohrid. The lake deepened gradually, with a relatively constant vertical displacement rate of ~0.2 mm a −1 between the central and the eastern lateral basin and with greater water depth presumably during interglacial periods. Although the dynamic environment characterized by local processes and the fragmentary chronology of the basal sediment successions from both sites hamper palaeoclimatic significance prior to the existence of a larger lake, the new data provide an unprecedented and detailed picture of the geodynamic evolution of the basin and lake that is Europe's presumed oldest extant freshwater lake.